Comparison of Ultrasound-guided Intra-articular Injection of Platelet-rich Plasma and Triamcinolone Acetonide in the Reduction of Pain and Functional Improvement in Primary Temporomandibular Joint Osteoarthritis: A Randomised Controlled Trial - Shruti Pandey; Longjam Nilachandra Singh; Akoijam Joy Singh; Monica Moirangthem; S. U. Priyanka (Indian Journal of Physical Medicine & Rehabilitation)
Background: Temporomandibular joint osteoarthritis (TMJ OA) is a degenerative condition leading to pain and functional impairment, commonly affecting the global population, with a higher prevalence in regions like India. Treatment options include non-invasive therapies and more invasive interventions, such as intra-articular (I/A) injections of corticosteroid and platelet-rich plasma (PRP). Objective: This study aimed to compare the efficacy of ultrasound-guided PRP and triamcinolone acetonide injections in reducing pain and functional improvement in patients with primary TMJ OA. Materials and Methods: A randomised controlled trial was conducted in the Department of Physical Medicine and Rehabilitation at the Regional Institute of Medical Sciences, Imphal, from August 2022 to July 2024. Thirty-eight patients with computed tomography-diagnosed TMJ OA were recruited and randomly assigned to receive either ultrasound-guided triamcinolone acetonide (Group A) or PRP injections (Group B). Outcome measures, including the Visual Analogue Scale (VAS), Maximum Mouth Opening (MMO) and Mandibular Function Impairment Questionnaire were assessed at baseline and 1 week, 4 weeks, 12 weeks and 24 weeks. Post-intervention data were analysed using SPSS version 21, with significance at P < 0.05. Results: Both the treatment groups showed significant improvements in pain and function. However, the PRP group demonstrated more substantial and sustained benefits. By 24 weeks, the PRP group exhibited a significant reduction in VAS scores (from 6.68 to 0.0, P < 0.05) and improvement in MMO (from 2 to 3.34 fingerbreadths, P < 0.05). In contrast, the corticosteroid group improved initially, but VAS scores returned to near-baseline levels (6.4) by 24 weeks. Conclusion: Ultrasound-guided I/A PRP injection is a safe and effective treatment for TMJ OA, providing longer-lasting pain relief and functional improvement compared to triamcinolone acetonide. Further studies with larger sample sizes and extended follow-up periods are recommended to validate these findings.